Highly efficient removal of hexavalent chromium from aqueous solution by calcined Mg/Al-layered double hydroxides/polyaniline composites - Long, Feng-Lan; Niu, Cheng-Gang; Tang, Ning; Guo, Hai; Li, Zhong-Wu; Yang, Ya-Ya; Lin, Li-Shen (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •The organic–inorganic hybrid materials were fabricated by a simple in situ oxidative polymerization.•The maximum adsorption capacity of Cr(VI) on PANI/LDOs was 409.77 mg/g at pH 2.•The reaction mechanism for the removal of Cr(VI) was proposed.•PANI/LDOs was a promising material for Cr(VI)-containing pollution remediation. In this study, the organic–inorganic hybrid materials of polyaniline/Mg-Al layered double oxides (PANI/LDOs) were synthesized by a simple in situ oxidative polymerization. PANI/LDOs have been researched via various characterization technologies and used to remove hexavalent chromium (Cr(VI)) from aqueous solutions. The influences of adsorption kinetics, isotherms, pH, coexisting ion types and strength on Cr(VI) removal were systematically studied. The results indicated that the existence of LDOs reduced the accumulation density of PANI and enhanced the specific surface area, which is beneficial to absorb Cr(VI) by PANI/LDOs. Kinetic studies reveal that the Cr(VI) adsorption onto PANI/LDOs was well fitted by the pseudo-second-order model. The isotherms were well simulated by Langmuir model, and the maximum adsorption capacity of Cr(VI) on PANI/LDOs reached 409.77 mg/g at pH ~ 2.0, which was superior to those of conventional adsorbents. Thermodynamic data revealed that the process of removing Cr(VI) was spontaneous and endothermic. The interaction mechanisms between PANI/LDOs and Cr(VI) were studied, indicating that Cr(VI) (HCrO4- and Cr2O72- were the main species when the aqueous solution pH 2) were reduced to Cr(III) through –NH-/=N- groups after uptaking to the protonated active sites of PANI/LDOs via electrostatic attraction. Furthermore, the PANI/LDOs composites can be regenerated and used repeatedly more than five cycles without significantly reducing in its adsorption capacity. All these results demonstrated that the fabricated PANI/LDOs possess great potentiality for Cr(VI)-containing wastewater treatment.